Anomalous 1992 spring and summer right whale (Eubalaena glacialis) distributions in the Gulf of Maine - Kenney, Robert D. (J. Cetacean Res. Manage., 2020)
No right whales (Eubalaena glacialis) were sighted during aerial surveys in May-July 1992 in the Great South Channel region of the southwestern Gulf of Maine. This was the first year that spring surveys failed to detect right whales in this region. During the late spring/early summer season when right whales would normally be expected in the Great South Channel, a few were sighted in the central Gulf of Maine, none were found in their usual late summer/early autumn feeding areas near Nova Scotia and a few were seen in Massachusetts Bay. The absence of right whales in the Great South Channel in 1992 can be attributed to a shift in the regional zooplankton community. The usual spring zooplankton of the region is strongly dominated by the calanoid copepod Calanus finmarchicus, vertically and horizontally aggregated into dense patches which are the preferred foraging areas of right whales. The 1992 zooplankton was dominated by pteropods, distributed evenly throughout the water column. It is possible, although unlikely, that pteropods are unacceptable prey for right whales. A more likely explanation is that their local densities within small-scale patches were below the energetic threshold required for successful right whale feeding. The shift in zooplankton dominance in 1992 is likely related to significantly reduced water temperatures and a delay in the development of the usual hydrographic structure of the region. The 1992 temperature and hydrographic anomalies, in turn, can be attributed principally to an unusually large influx of colder and fresher Scotian Shelf Water, and may have been enhanced by widespread cooling of the Northern Hemisphere caused by sulphuric acid haze in the atmosphere from the June 1991 eruption of Pinatubo volcano in the Philippines.